(untitled) (Perner’s Contacts, 2012)
This paper shows intermodal load distribution diagram of maritime container loaded on intermodal wagon and container chassis. Technical characteristics of container are compared with technical characteristics of the wagon and container chassis. Intermodal road – rail - sea load distribution diagram meets conditions of relevant transport modes specific to Europe.